A Large Parasitic Dermoid Cyst in The Pouch of Douglas, A Torsion Complication? Parasitic Dermoid Cyst in Douglas Pouch - Luay Abu Atileh; Nouf Khalifeh (Indonesian Journal of Obstetrics and Gynecology, 2021)
Abstract Objectives: To identify the underlying etiology of dermoid cysts in the pouch of Douglas. Case presentation: A 44-year-old woman presented to our clinic complaining of chronic, dull-aching lower abdominal pain of one-month duration. Pelvic ultrasound examination showed an eight-centimeter cystic appearing lesion in the right adnexa. Computed tomography (CT) suggested the diagnosis of dermoid cyst. Laparoscopy revealed a residual ovarian tissue on the right side and an eight-centimeter cystic mass occupying the pouch of Douglas. The entire specimen was removed en bloc through the umbilicus incision inside a bag with no spillage. Histopathologic examination confirmed the diagnosis of a mature cystic teratoma. Conclusion: Parasitic dermoid cysts are extremely rare entity especially those located in the pouch of Douglas. Autoamputation and reimplantation is the most accepted etiology to explain this phenomenon. Key-words: Autoamputation, dermoid cyst, Douglas, Laparoscopy, Mature cystic teratoma